2011
DOI: 10.1007/s00248-011-9976-7
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Elemental Release During the Granite Dissolution Can Be Changed by Aerobic Heterotrophic Bacterial Strains Isolated from Damma Glacier (Central Alps) Deglaciated Granite Sand

Abstract: Colonisation and weathering of freshly deglaciated granite are key processes in initial soil formation and development. We have obtained 438 isolates from granite sand covering glacial toe, 284 isolates at 22°C and 154 at 4°C incubation temperatures, respectively, to obtain cultures for the investigation of their weathering capabilities under laboratory conditions. The isolation of bacteria from granite sand was performed on rich-, intermediate- and low-nutrient-content solid media. Isolates were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 83 publications
2
37
0
3
Order By: Relevance
“…In contrast, representatives of Bacteroidetes, Actinobacteria, and Proteobacteria were significantly enriched in our study for all mineral types considered. Notably, these taxa have been repeatedly detected on mineral or rock surfaces such as granite, volcanic basaltic glass, marine basalts, or pure particles of apatite (33,(46)(47)(48), indicating that they may be adapted to colonize and inhabit rock and mineral surfaces in terrestrial and aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, representatives of Bacteroidetes, Actinobacteria, and Proteobacteria were significantly enriched in our study for all mineral types considered. Notably, these taxa have been repeatedly detected on mineral or rock surfaces such as granite, volcanic basaltic glass, marine basalts, or pure particles of apatite (33,(46)(47)(48), indicating that they may be adapted to colonize and inhabit rock and mineral surfaces in terrestrial and aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the ability to weather minerals has been demonstrated for a large range of bacterial strains isolated from various environments such as the rhizosphere of several plants (10,32,39,49) and granite samples from the Damma glacier (19,30). This ability was notably reported for bacteria belonging to the Arthrobacter, Bacillus, Burkholderia, and Collimonas genera (3,19,33,46,51,56,57).…”
mentioning
confidence: 98%
“…Due to their nutritive value, minerals can be considered a true ecological habitat giving excellent physical support for the development of specific microbial communities (8,11,12,21,30,43,54). As an example, Gleeson et al (21) demonstrated that the taxonomic structure of the bacterial communities colonizing granite minerals was not homogenous and varied in relation with the mineral crystals (muscovite, plagioclase, K-feldspar, and quartz) present in this granite.…”
mentioning
confidence: 99%
“…This was investigated in mineral dissolution experiments using bacterial isolates from the Damma forefield (Lapanje et al, 2012). Selected isolates were screened for high mineral dissolution potential; however, the abiotic controls using citric and hydrochloric acid released elements at significantly higher rates than the bacterial isolates did (Lapanje et al, 2012). Future studies need to investigate the P release from mineral bedrock in the initial soils, as the mechanisms have not been studied in detail, but are crucial for the development of the ecosystem.…”
Section: Development Of Initial C and N Cyclesmentioning
confidence: 99%
“…The dissolution of P and other nutrients from the minerals might be accelerated by microorganisms releasing organic acids or chelators. This was investigated in mineral dissolution experiments using bacterial isolates from the Damma forefield (Lapanje et al, 2012). Selected isolates were screened for high mineral dissolution potential; however, the abiotic controls using citric and hydrochloric acid released elements at significantly higher rates than the bacterial isolates did (Lapanje et al, 2012).…”
Section: Development Of Initial C and N Cyclesmentioning
confidence: 99%